Twelve Augusti. (8th June 2018) - Goodman, Penelope J.
Abstract : A rash of new festivals, a fashion for calendars and a renamed month all attest to the strength of anniversary culture in the Augustan era, and to Augustus' own facility for capitalising upon it. We can safely assume that he would have understood, and perhaps even anticipated, that the bimillennium of his death might be commemorated. Whether he would quite have expected the exhibitions, conferences and publications with which twenty-first-century academics chose to mark it is perhaps another matter. This review article examines some of the scholarly fruits of Augustus' 2014 anniversary, encompassing twelve books which were published that year, took it as an explicit prompt or were developed out of bimillennial conferences. They are tackled in three broad groups, the better to bring out the characteristic interests and approaches of each.